(84-(56+(3×8)÷(2+4+5-1)))×2
Soluções para a tarefa
Respondido por
0
Resposta: 51,2
Explicação passo a passo:
(84-(56+(3×8)÷(2+4+5-1)))×2
1° - (2+4+5-1) = 10
2° -(3×8) = 24
(84-(56+ 24÷10))×2
3° - 24÷10= 2,4
(84-(56+ 2,4))×2
4°- 56 + 2,4= 58,4
(84- 58,4 ) ×2
5° - 84 - 58,4 = 25,6
25,6 × 2 = 51,2
Resposta 51,2
bons estudos!
Perguntas interessantes
Geografia,
6 meses atrás
Física,
6 meses atrás
Informática,
6 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Saúde,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás